2017
DOI: 10.1007/s11207-017-1080-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Reconnection Flux Using Post-eruption Arcades and Its Relevance to Magnetic Clouds at 1 AU

Abstract: We report on a new method to compute the flare reconnection (RC) flux from post-eruption arcades (PEAs) and the underlying photospheric magnetic fields. In previous works, the RC flux has been computed using cumulative flare ribbon area. Here we obtain the RC flux as half of that underlying the PEA associated with the eruption using an image in EUV taken after the flare maximum. We apply this method to a set of 21 eruptions that originated near the solar disk center in Solar Cycle 23. We find that the RC flux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 44 publications
(71 reference statements)
5
62
0
Order By: Relevance
“…It is possible to test this flux relationship using solar and interplanetary data since the ejected flux ropes at the Sun are detected in situ in the solar wind as magnetic clouds (MCs) (Burlaga et al 1981;Goldstein et al 1983;Klein and Burlaga, 1982). Qiu et al (2007) confirmed that the RC flux at the Sun is about the same as the poloidal flux of the corresponding MC at 1 au (see also Moestl et al 2009;Hu et al 2014;Gopalswamy et al 2017). Qiu et al (2007) determined the RC flux as the photospheric magnetic flux underlying the area swept up by the flare ribbons on one side of the polarity inversion line.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…It is possible to test this flux relationship using solar and interplanetary data since the ejected flux ropes at the Sun are detected in situ in the solar wind as magnetic clouds (MCs) (Burlaga et al 1981;Goldstein et al 1983;Klein and Burlaga, 1982). Qiu et al (2007) confirmed that the RC flux at the Sun is about the same as the poloidal flux of the corresponding MC at 1 au (see also Moestl et al 2009;Hu et al 2014;Gopalswamy et al 2017). Qiu et al (2007) determined the RC flux as the photospheric magnetic flux underlying the area swept up by the flare ribbons on one side of the polarity inversion line.…”
Section: Introductionmentioning
confidence: 65%
“…In order to do this, we compute the RC flux from source regions using the PEA technique recently developed by Gopalswamy et al (2017). According to this method, the RC flux is computed as half the unsigned photospheric magnetic flux underlying PEAs in the source region.…”
Section: Data Selectionmentioning
confidence: 99%
See 3 more Smart Citations